2021
DOI: 10.1111/ijd.15991
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic diet‐induced prurigo pigmentosa: a rising association

Abstract: Prurigo pigmentosa (PP) is an uncommon inflammatory dermatosis first described in 1971. It is characterized by recurrent crops of pruritic erythematous papulovesicles that resolve with a macular reticulated hyperpigmentation. The exact etiology is yet to be determined, however with the expanded application of the ketogenic diet (KD) in recent years, conditions accompanied with ketosis are more commonly being described in association with PP. Antibiotics as well as resolution of ketosis can effectively treat th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Social media sites describe this as "the keto rash," and although generally rare, dermatologists have noted an apparent increase in prevalence over the past 7 years, attributing this to the increased popularity of the LCHF diet. 28 Although the etiology is unknown, it has been associated with other scenarios of ketosis including poorly controlled diabetes, fasting, anorexia nervosa, or bariatric surgery. 29 A recent systematic review of 369 case studies included in 118 papers reported that of the 25% of patients who reported that dietary changes preceded the onset of the rash, 40% were associated with a ketogenic LCHF diet.…”
Section: Discussionmentioning
confidence: 99%
“…Social media sites describe this as "the keto rash," and although generally rare, dermatologists have noted an apparent increase in prevalence over the past 7 years, attributing this to the increased popularity of the LCHF diet. 28 Although the etiology is unknown, it has been associated with other scenarios of ketosis including poorly controlled diabetes, fasting, anorexia nervosa, or bariatric surgery. 29 A recent systematic review of 369 case studies included in 118 papers reported that of the 25% of patients who reported that dietary changes preceded the onset of the rash, 40% were associated with a ketogenic LCHF diet.…”
Section: Discussionmentioning
confidence: 99%
“…PP has gradually been reported from many different places around the world suggesting different pathogenesis than originally proposed by the Japanese dermatologist Masaharu Nagashima [1], who first described the condition in Japan in 1971. PP has been associated with Helicobacter pylori infection [2], nutrition [3] and especially ketogenic diets [4][5][6][7], weight loss, and anorexia nervosa [8]. In a review by Böer et al [9], they conclude that PP is highly distinctive clinically, histopathologically, and biologically, and the group raises question marks to all factors mentioned as being causative of PP due to short follow-up, incomplete and imprecise histopathology descriptions of biopsies performed in both early and late stages of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although the etiology of PP is not clearly understood, perivascular accumulation of ketone bodies is thought to trigger a neutrophilic infiltration [ 2 ]. There is a growing association of PP with ketosis, with 25% of patients having a history of dietary changes [ 2 , 4 ]. In our series, this association was striking with history of diet changes prior to development of PP in 75% of the patients.…”
Section: Discussionmentioning
confidence: 99%